2010
DOI: 10.1289/ehp.0901340
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to PBDEs and Neurodevelopment

Abstract: BackgroundPolybrominated diphenyl ethers (PBDEs) are widely used flame retardant compounds that are persistent and bioaccumulative and therefore have become ubiquitous environment contaminants. Animal studies suggest that prenatal PBDE exposure may result in adverse neurodevelopmental effects.ObjectiveIn a longitudinal cohort initiated after 11 September 2001, including 329 mothers who delivered in one of three hospitals in lower Manhattan, New York, we examined prenatal PBDE exposure and neurodevelopment when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
399
5
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(427 citation statements)
references
References 47 publications
18
399
5
5
Order By: Relevance
“…Exposure to pentaBDE in umbilical cord blood is associated with adverse neurodevelopmental effects in children [58]. Children in the highest 20 % of the exposure distribution showed lower IQ performance scores (ranging from 5 to 8 points lower) at all ages [58].…”
Section: Developmental Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to pentaBDE in umbilical cord blood is associated with adverse neurodevelopmental effects in children [58]. Children in the highest 20 % of the exposure distribution showed lower IQ performance scores (ranging from 5 to 8 points lower) at all ages [58].…”
Section: Developmental Effectsmentioning
confidence: 99%
“…Children in the highest 20 % of the exposure distribution showed lower IQ performance scores (ranging from 5 to 8 points lower) at all ages [58]. In the Netherlands, prenatal exposure to pentaP-BDE was associated with significant adverse effects on motor, cognitive, and behavioral outcomes in the children [59].…”
Section: Developmental Effectsmentioning
confidence: 99%
“…For instance, PBDEs (BDE-47, -99, and -100) measured in umbilical cord blood of women have been found to be correlated with reduced performance of gestationally-exposed children (aged 0-6) on mental performance tests. 207 Moreover, maternal prenatal and childhood PBDE exposures have been associated with reduced attention, fine motor coordination, and cognition (declines in IQ scores) among a California cohort of MexicanAmerican children. 64 A substantial number of studies in rodents, spanning different laboratories, have demonstrated also that PBDEs can elicit adverse neurobehavioral outcomes in early development.…”
Section: Toxicity Mechanisms and Thyroid Interactionsmentioning
confidence: 99%
“…It is suggested that exposure to PBDE during this period affects normal neurodevelopment. Herbstman et al [30] investigated prenatal PBDE exposure and child neurodevelopment. Their study population were 329 women who on 11 September 2001 were pregnant and delivered in hospitals placed at most 2 miles from the zero ground (World Trade Center) in New York.…”
Section: Human Studiesmentioning
confidence: 99%
“…After birth the pups were examined for developmental landmarks (eruption of incisors, fur development, eye opening and testes descent), postnatal reflex (spontaneous cliff-drop aversion reflex and ability to stay on a rotating rod for 3 min.s at 7 rpm), locomotor activity as well as reproductive characteristics (spermatid number, sperm count and morphology, testosterone and luteinizing hormone (LH) levels). There were no differences between the control group and the PBDEs treated rats in the age concerning fur of age the Wechsler Preschool and Primary Scale of Intelligence, Revised Edition (WPPSI-R) was carried out [30]. Authors found that women who lived closer to the ground zero in New York on September 11 did not have higher blood concentration of PBDEs; however, cord blood concentration of PBDEs depended on time of delivery: women who delivered sooner after September 11 had higher concentration of PBDEs [30].…”
Section: Animal Studiesmentioning
confidence: 99%